English Teachers’ Challenges in Managing Classroom during Online Learning at SMAN 13 Padang - Chindy Selvia; Zul Amri (Journal of English Language Teaching, 2023)
Since Covid-19 outbreak, Indonesia government shifts the learning system from conventional into online learning to stop the spread of Covid-19. This situation causes new challenges for teacher in teaching and learning process, especially in classroom management. The aim of this study is to explore the challenges faced by teachers in the classroom during teaching and learning process. Qualitative descriptive method is used in this research. The samples of this study are English teachers at SMAN 13 Padang. The numbers of English teachers at SMAN 13 Padang are four. The data was collected through questionnaire (close question) and interview (open question). The result of this study revealed that there were some challenges in managing classroom during online learning. Students participation is the first challenge that teacher deal with. For example, students not listen to teacher explanation. The other challenge is students’ misbehavior which becomes significants problem must be addressed such as late and not stay in the room. During online learning process, students often did not pay attention with teacher in the classroom.